Inflammatory Bowel Diseases and Sarcopenia: The Role of Inflammation and Gut Microbiota in the Development of Muscle Failure - Nardone, Olga Maria; de Sire, Roberto; Petito, Valentina; Testa, Anna; Villani, Guido; Scaldaferri, Franco; Castiglione, Fabiana (Frontiers in Immunology, 2021)
Sarcopenia represents a major health burden in industrialized country by reducing substantially the quality of life. Indeed, it is characterized by a progressive and generalized loss of muscle mass and function, leading to an increased risk of adverse outcomes and hospitalizations. Several factors are involved in the pathogenesis of sarcopenia, such as aging, inflammation, mitochondrial dysfunction, and insulin resistance. Recently, it has been reported that more than one third of inflammatory bowel disease (IBD) patients suffered from sarcopenia. Notably, the role of gut microbiota (GM) in developing muscle wasting in IBD patient is a matter of increasing interest. It has been hypothesized that gut dysbiosis, that typically characterizes IBD, might alter the immune response and host metabolism, promoting a low-grade inflammation status able to up-regulate several molecular pathways related to sarcopenia. Therefore, we aim to describe the basis of IBD-related sarcopenia and provide the rationale for new potential therapeutic targets that may regulate the gut-muscle axis in IBD patients.